Consumer ethnocentrism: bibliometric analysis and literature review through cognitive structure and mapping of research based on web of science (WoS) and scopus - Marcela Yonfá-Medranda; David Sabando-Vera; Jesús Pérez-Gálvez; Carol Jara-Alba (Cogent Business & Management, 2024)
Research on consumer ethnocentrism (CE) has increased worldwide in various academic disciplines and business sectors due to the rise of globalization and cross-border trade in goods and services. There are few studies that review the literature on CE, all of which can be improved in terms of their degree of objectivity, systematization and number of publications used. The main objective of this paper is to contribute to the academic literature on CE. A broad spectrum of 670 indexed articles from the union of WoS and Scopus was used. We use R and VOSviewer to process the data. We follow a methodological organization according to the 5 W + 2H review framework, the Scientific Procedures and Rationale for Systematic Reviews of the Literature (SPAR-4-SLR) protocol. A bibliometric analysis of keyword co-occurrence in conjunction with the Theory framework. Context, Characteristics and Methodology (TCCM). There is a growing trend in scientific production, with contributions from 82 countries, 1292 authors and 281 sources, with the United States leading the way, followed by Australia and India. The cognitive structure is made up of topics such as consumer ethnocentrism, country of origin, marketing strategies, branding, consumer behavior in marketing, consumer attitude, and consumer animosity. This work provides an objective and scientifically rigorous basis for reducing researcher bias in literature reviews. In addition, it improves the formulation of marketing and commerce strategies by business or public policy decision-makers. The implications and limitations of the study are presented, and future lines of research are suggested.
Keywords: 650; Bibliometric analysis; consumer ethnocentrism; consumer behavior; consumer research; international marketing